Research on circadian clock genes in non-small-cell lung carcinoma. (3rd June 2019) - Qiu, Mengjun; Chen, Yao-bing; Jin, Si; Fang, Xie-fan; He, Xiao-xiao; Xiong, Zhi-fan; Yang, Sheng-li
ABSTRACT: Circadian clock genes have become a hot topic in cancer research in recent years, and more and more studies are showing that clock genes are involved in regulating cell proliferation cycle and apoptosis of malignant tumors, neuroendocrine and immune function, and other processes. Lung cancer is a malignant tumor with increasing incidence worldwide. The pathogenesis of lung cancer is extremely complicated and includes genetic factors, living environment, and smoking, and the occurrence of lung cancer is related to the regulation of many oncogenes and tumor suppressor genes. But there are few studies on clock genes in lung cancer. Studies on clock genes may help to better understand the mechanism of lung cancer development for an improved treatment. The expressions of all 14 kinds of clock genes in adenocarcinoma (ADC) and squamous cell carcinoma (SCC), two main kinds of non-small-cell lung cancer (NSCLC), were studied based on integration and analysis of data from The Cancer Genome Atlas (TCGA) to show the association between clock gene expression and prognosis of cancer patients. Analysis of TCGA data indicated that overexpression of Cry2, BMAL1, and RORA with underexpression of Timeless and NPAS2 was associated with a favorable prognosis of ADC, and the expression of NPAS2 was associated with the time of patient survival. Additionally, the expression of Cry2 was related to TNM stage. In SCC, high expression of DEC1 was correlated with poor overall survival in patients and the expression of Timeless was associated with the time of patient survival. In NSCLC, circadian clock genes constitute cancer circadian rhythm by interacting with each other, showing that asynchrony with normal tissues, which collectively controlling the occurrence and development of NSCLC.